PENERAPAN MODEL KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATIONMATERIPELUANG MTs TI AL-MADANI PONTIANAK - Priantini, Eriska; Halini, Halini; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to find and to describe the effectiveness of learning by applying the cooperative learning model type Team Assisted Individualization for opportunity material at MTs TI Al-Madani in Pontianak. The research method used pre-eksperimental method with one-shot case study design. 16 students of 8th B MTs TI Al-Madani Pontianak were taken as the research subyek The indicators used to determine the effectiveness of learning using the Team Assisted Individualization cooperative learning model are: learning implementation, students learning activities, and students learning outcomes. Data collection techniques are measurement techniques and direct observation techniques. The data collection tools are, the learning outcome test, the learning implementation observation sheet and the students activity observation sheet. The result of implementation of learning is classified as good, the learning activities of students were classified as active, and the learning outcomes of students were not complete.The application of the student teams achievement divisions type of cooperative learning model on opportunity material at MTs TI Al-Madani Pontianak is ineffective.Keyword: Application Of Learning, Team Assisted Individualizatio Type Of Cooperative Model, Opportunity Material